Improving hardware/software interface management in systems of systems through documentation as code (2023)
Context: The management of Interface Control Documents (ICDs) has shown to be a major pain point in the architecting processes of Systems of Systems (SoS). Objective ThisworkaimstoimproveonpreviouslyidentifiedICDmanagementissuesusing the documentation-as-code philosophy as a potential basis for a treatment, and in collaboration with practitioners. Method: Weconducted a Technical Action Research (TAR) study with a group of engineers at the Netherlands Radio Astronomy Institute (ASTRON), in the context of the LOFAR radio telescope. An additional research instrument, in the form of an expert panel, was used to evaluate the transferability of the proposed treatment to alternative domains. Results: In-depth insights on previously identified interface management issues were gained. Based on these insights a functional proof-of-concept was developed aimed at addressing these issues following the documentation-as-code principles. In addition to receiving overall positive reviews from practitioners and experts, further areas of improvement and transferability considerations for future work were identified. Conclusions: The proposed approach, which to our knowledge has not been explored before in this context, is promising to address some of the recurring interfacing-related issues with directed SoS in multiple engineering domains. This could be done mainly by enforcing consistency and completeness on both text-based and formal elements of the ICDs, and turning ICDs into single sources of truth for the architecting processes of large scale SoS.